Determination of atypical antipsychotics in human plasma by UPLC-UV with polystyrene nanofibers as a solid-phase extraction sorbent. Issue 25 (31st May 2022) - Fan, Liju; An, Jing; Gao, Jin; Cui, Yanjun; Dong, Zhanjun
Abstract : A novel extraction procedure was developed using electrospun polystyrene (PS) nanofibers as a solid-phase extraction sorbent to collect atypical antipsychotics (AAPs) from human plasma. Abstract : A novel extraction procedure was developed using polystyrene (PS) nanofibers as a solid-phase extraction sorbent to collect atypical antipsychotics (AAPs) from human plasma. The extraction targets were then monitored by ultra high performance liquid chromatography with an ultraviolet detector system. Parameters affecting extraction efficiency such as fiber packing amount, wash solution, and eluted solvent were investigated. Under optimized conditions, the linear range of seven AAPs was 1–50 μgmL −1 ( R 2 > 0.996). Inter-day and intra-day relative standard deviations were less than 15.1%, and relative error varied from −17.1% to 12.0%. Furthermore, 50.5–79.3% extraction recoveries were obtained. The lower limit of quantification was 1 μg mL −1, and detection limit was 0.5 μg mL −1 . The method developed in this study may be applied to simultaneous quantification of seven AAPs in human plasma due to its simplicity, selectivity, and efficiency.